1998
DOI: 10.1139/f98-035
|View full text |Cite
|
Sign up to set email alerts
|

Improving the stock-recruitment relationship in Icelandic cod (Gadus morhua) by including age diversity of spawners

Abstract: The size of the Icelandic cod stock has been gradually declining since the middle of this century. Recruitment has been poor over an extended period of time and much below the long-term average since 1985. Except for the concurrent decrease in stock size and recruitment during this period, the stock size - recruitment relationship is weak. This relationship is improved by including the age composition of the spawning stock. Spawning stock age diversity in each year from 1955 to 1992 was estimated with the Shan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
176
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(184 citation statements)
references
References 18 publications
5
176
1
Order By: Relevance
“…5b). Similar observations were made by Marteinsdottir and Thorarinsson (1998) who detected that inclusion of a stock age diversity index in Icelandic cod assessment improved the stock-recruitment relationship, and variation of recruitment explained by the model increased from 15% to 31% when age composition was considered. Furthermore, Saborido-Rey et al (2004) not only analysed effects of including age composition of spawner stock in stock-recruitment models, but also considered sex ratio and presence of skip spawners that directly affected estimates of SSB; it was observed that recruitment predictions improved when these variables were included in the model.…”
Section: Changes In Maturity In Response To Fishing Pressuresupporting
confidence: 82%
See 1 more Smart Citation
“…5b). Similar observations were made by Marteinsdottir and Thorarinsson (1998) who detected that inclusion of a stock age diversity index in Icelandic cod assessment improved the stock-recruitment relationship, and variation of recruitment explained by the model increased from 15% to 31% when age composition was considered. Furthermore, Saborido-Rey et al (2004) not only analysed effects of including age composition of spawner stock in stock-recruitment models, but also considered sex ratio and presence of skip spawners that directly affected estimates of SSB; it was observed that recruitment predictions improved when these variables were included in the model.…”
Section: Changes In Maturity In Response To Fishing Pressuresupporting
confidence: 82%
“…SSB and females only SSB were estimated from mean weight at age in the catch (as used by the Working Group) and the two abundance data sets described above, together with the maturity ogives specifically estimated for this analysis. The age diversity of the spawning stock was estimated using the Shannon diversity index (Marteinsdottir and Thorarinsson 1998):…”
Section: Biological Datamentioning
confidence: 99%
“…The truncated age distributions commonly seen in heavily fished populations are known to negatively affect parental quality (47) and thereby recruitment success (48). If this holds true for the BS cod, positive changes in recruitment should become apparent in the near future as a consequence of the higher stock-age diversity (49). Furthermore, having a wider range of reproductive age classes may buffer against factors influencing recruitment variability (e.g., ref.…”
Section: Temperature-driven Range Expansions and Bs Cod Population Sizementioning
confidence: 99%
“…For example, it is now evident that variations in stock structure and condition of the adults can affect the level of egg production (Marshall et al 1998;Marteinsdottir and Thorarinsson 1998;Marshall and Frank 1999) and impact on egg viability and buoyancy. Variations in egg viability and buoyancy influence the survival probability of eggs and larvae (e.g., Kjesbu et al 1996;Nissling et al 1998;Trippel 1998) and, combined with variations in stock reproductive effort, are targeted as being responsible for recruitment fluctuations (Marshall et al 1998;Marteinsdottir and Thorarinsson 1998;Jarre-Teichmann et al 2000). Furthermore, the effects of predation on fish eggs and larvae (e.g., Bailey and Houde 1989) have the potential to reduce the reproductive success of a stock.…”
Section: Introductionmentioning
confidence: 99%